Analisis Juridis Konversi Status Ikatan Jual Beli Menjadi Kewajiban Hukum Repayment Berdasarkan Akta Perdamaian Dalam Putusan Nomor 252/Pdt. G/2020/Pn Kpg - Nurkholifah Nurkholifah; Juliana Susantje Ndolu; Husni Kusuma Dinata (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the legal conversion of a Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli/PPJB) into a legal repayment obligation based on a deed of settlement in Decision Number 252/Pdt.G/2020/PN Kpg, as well as the legal consequences arising from failure to fulfill such obligation. This research employs normative legal methods using statutory, conceptual, analytical, and case approaches. Legal materials were collected through library research and analyzed using descriptive qualitative methods. The findings indicate that the binding sale and purchase agreement constitutes a preliminary contract creating only obligatory rights and obligations without transferring land ownership. Through a court-approved deed of settlement, the parties' legal relationship was converted into a repayment obligation as a form of novation consistent with the principle of freedom of contract and the provisions of the Indonesian Civil Code. The settlement deed possesses the same legal force as a final court judgment and is enforceable upon default. Failure by either party to comply with the settlement agreement may result in default, compensation, execution of the judgment, and enforcement against collateral, thereby ensuring legal certainty and protection for the parties.